WWP2 ameliorates acute kidney injury by mediating p53 ubiquitylation and degradation. (5th April 2020) - Che, Hong; He, Weilai; Feng, Junbo; Dong, Wenpeng; Liu, Shandong; Chen, Tao; Ge, Shenglin; Zhou, Jun; Liang, Chaozhao
Abstract : E3 ubiquitin ligase gene, WWP2, is associated with acute kidney injury (AKI). This research was conducted to explore the role of WWP2 in AKI. AKI cell model was produced in human renal proximal tubular epithelial cell line (HK‐2) by ischemia‐reperfusion (IR) injury. CCK8 and flow cytometry assay were performed to explore the influence of WWP2 overexpression on cell proliferation and apoptosis of IR‐induced HK‐2 cells. Quantitative real‐time PCR and immunoblotting (IB) were performed to assess the gene and protein expression. Then, the influence of WWP2 on p53 ubiquitylation and degradation was estimated by immunoprecipitation assay. Our data indicated that WWP2 was down‐regulated and p53 was up‐regulated in IR‐induced HK‐2 cells. WWP2 overexpression promoted proliferation and inhibited apoptosis of IR‐induced HK‐2 cells. And WWP2 interacted with p53 and regulated p53 ubiquitylation and degradation. Furthermore, the influence of WWP2 on cell proliferation and apoptosis was rescued by MG132 (proteasome inhibitor) treatment. In conclusion, our work described for the first time the role of WWP2 in AKI, showing that WWP2 ameliorated AKI by mediating p53 ubiquitylation and degradation. Moreover, the study offers some important insights into the occurrence of AKI and WWP2 may be a novel target of AKI treatment. Significance of the study: Our data elaborates that WWP2 has protective effect against AKI by mediating p53 ubiquitylation and degradation. Thus, WWP2 might be a therapeutic target for AKI.